Adaptation and validation of the motivated strategies for learning questionnaire for Dutch pre-vocational students - Bernard Brouwer; Matthijs J. Warrens; Hanke Korpershoek (Empirical Research in Vocational Education and Training)
Abstract To study self-regulated learning in pre-vocational education, researchers need instruments that have high reliability and validity. This study investigated, for the first time, the factorial validity and reliability of the Motivated Strategies for Learning Questionnaire (MSLQ) for students in pre-vocational education in the Netherlands. The MSLQ was administered to 594 Dutch pre-vocational students. Reliability analyses of the MSLQ sections and subscales were conducted. Furthermore, confirmatory factor analysis was used to test the factor structures of the MSLQ sections, scales and subscales. High reliability was found for both sections of the MSLQ, i.e., the sections Motivation and Learning Strategies, but varying levels of reliability were obtained for the fifteen MSLQ subscales. With regard to factorial validity, a moderate to good model fit for most subscales was found. For some subscales, certain modifications were required to obtain a good model fit. Each of the modifications made could be justified substantially. Furthermore, for two subscales the factor model was exactly identified and factor validity could not be studied. For most MSLQ subscales, evidence was found that the constructs measured with these subscales can be assessed quite well among Dutch pre-vocational students. However, scores based on the complete MSLQ or the two sections should not be used.